The real Malay pen pictures - Swettenham, Frank Athelstane Sir 1850-1946 (Silverfish Malaysian classics, 2019)
Swettenham was the first British Resident-General of the Federated Malay States at the end of the nineteenth century. Like many colonial administrators he found time to write about his impressions of the country where he was based. This is a collection of musings, anecdotes and short essays about what he thought of Malaya and its peoples.